A Non-interactive Key Exchange Scheme for Space-IntegratedGround Information Network Based on Blockchain - Mengru LIU; Yulong FU; Jin CAO; Hui LI (天地一体化信息网络)
For scenarios such as space-integrated-ground information network where satellite resources are limited and communication delays are large, in response to the requirements of non-interactive key exchange in the satellite communication network, a non-interactive key exchange scheme for space-integrated-ground information network based on blockchain and Diffi e-Hellman key exchange protocol was proposed.The scheme arranged the blockchain in space-integrated-ground information network to form TDYTH blockchain.After the satellite node was registered, its related information was stored in TDYTH blockchain.When the satellite node needed to communicated with the long-distance node such as NCC, the two parties could query the immutable information stored in TDYTH blockchain to generated the shared session key, established consensus, and then completed access authentication and key distribution under non-interactive conditions.The result of simulation demonstrated that the scheme we proposed could meet the requirements of non-interactive key distribution of satellites and other nodes, and could signifi cantly improved security and robustness.